Dissertation as Strategy for the Teaching of Philosophy - Silva-Másmela, Eliaquín; Díaz, Juan Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article presents the results of the research project “The philosophical dissertation as a method for teaching philosophy”, which proposes strengthen the appropriation of concepts, oral expression, research, and structuring of students’ epistemological thought. The research was carried out from a qualitative approach, taking action research as a development axis, as it allows to identify, construct, improve and understand social practices in a self-reflective way, work on a concrete contextualized reality, test a hypothesis, and encourage the participation of the community under study. The proposal was developed through discussion groups, which enabled the active participation of students who generated significant knowledge and participated in their learning process.